DEVELOPMENT OF MEDIATION IN RUSSIA:: EXTRAPOLATION OF FOREIGN EXPERIENCE - A. Sorokoletova, Marina; S. Baeva, Svetlana; Yu. Kornyushkina, Alla; A. Kravets , Sergey; V. Stus, Nina (Gênero & Direito, 2020)
The article analyzes the development of mediation in Russia based on foreign experience. The Institute of mediation has passed a long way of development before it was established on a legislative basis and is still far from perfect. Many problems prevent the effective use of mediation. This institution cannot fully carry out the tasks assigned to it. Mediation has great potential to become a real alternative and at the same time effective way of resolving disputes in Russia, which is proved by examples of legislation in other countries and the practice of its application.